The use of mycophenolate mofetil in treating patients with non responding aplastic anemia - Gan, Gin Gin; Leong, C.F.; Sangkar, J.V.; Teh, A.; Goh, K.Y.; Cheong, S.K. (Malaysian Medical Association, 2005)
Aplastic anemia is a relatively uncommon disease and conventional management options include immunosuppressive drugs and/or haematopoeitic stem cell transplantation. It is now known that the pathogenesis of aplastic anemia is immune mediated. Mycophenolate mofetil is a common immunosuppressive drug now used mainly in prophylaxis of graft rejection in organ transplant and also for prevention/treatment for graft versus host disease in haemtopoeitic stem cell transplantation. It is thought that mycophenolate mofetil may be useful in this group of patients. In this short report, mycophenolate mofetil was tried in 6 patients who had severe aplastic anemia with variable doses for a minimum duration of 9 months. The result has however not been encouraging.